Konsep Peraturan Perundang-Undangan Tentang Kepastian Usia Prespektif Kedewasaan Perkawinan - Setiyawan, Deni; Kurniawan, Dimas Awal (JATIJAJAR LAW REVIEW, 2023)
There is still a discrepancy between the marriage boundaries between the KHI and the Marriage Law which can affect the chances of leniency in applying for a marriage dispensation because there is no legal certainty regarding marriage boundaries. Whereas the purpose of marriage is to form a sakinah, mawaddah, warahmah family. To achieve this, a mature character is needed to regulate household life and offspring.  From these problems, it is deemed necessary to conduct further research studies on the concept of maturity in marriage, what is the positive legal basis for the age of marriage? and how the law as a means of social control of early marriage? The method used in this study uses a normative juridical approach with a Statute Approach and a conceptual approach.The results obtained, that the concept of maturity in marriage can be seen from 3 perspectives, namely the positive law contained in Law No. 1 of 1974 which has been changed to Law No. 16 of 2019 concerning Marriage, but then from KHI still refers to the Marriage Law but also remains in accordance with the Qur'an and As-Sunnah and use the discretion of the judge through the ratio decided. Second, that the positive legal concept in early marriage has been regulated in Law No. 1 of 1974 which has been changed to Law No. 16 of 2019 concerning Marriage, article 7 paragraph (1) and in the KHI article 16 paragraph (1). Third, that the law is a tool for social engineering and as a tool to regulate human beings which is included in the Law concerning the age limit for marriage as a form of legal engineering to regulate early marriage. So with the law regarding the age of marriage, it is expected to reduce and provide education to the public about the impact and prohibition of early marriage. So that it will create certainty, benefit and legal justice